Green synthesis of gold nanoparticles from waste macadamia nut shells and their antimicrobial activity against Escherichia coli and Staphylococcus epidermis - Dang, Huu; Fawcett, Derek; Poinern, Gerrard Eddy Jai (International Journal of Research in Medical Sciences, 2019)
Background: The study for the first time demonstrates an eco-friendly and room temperature procedure for biosynthesizing gold (Au) nanoparticles from waste Macadamia nut shells. Currently Australia contributes around 40% to the global market and generates around AUS 150 million of export revenue. However, a consequence of large nut production is the generation of large quantities of waste nut shells. The green chemistry-based method is clean, nontoxic and eco-friendly. The method presented in this study produced a variety of Au nanoparticle sizes and shapes. Methods: The straightforward green chemistry-based technique used waste Macadamia nut shells to generate Au nanoparticles, which were subsequently studied using several advanced characterization techniques. Furthermore, the Kirby-Bauer sensitivity method was used to evaluate the antibacterial properties of the extracts and synthesized gold nanoparticles. Results: Advanced characterisation revealed the Au nanoparticles were crystalline, ranged in size from 50nm up to 2µm, and had spherical, triangular and hexagonal morphology. The gram-negative bacteria Escherichia coli produced a maximum inhibition zone of 11mm, while Staphylococcus epidermidis produced a maximum inhibition zone of 9mm. Conclusions: The study has shown that waste Macadamia nut shell extracts have no antibacterial activity, but the synthesised Au nanoparticles did display antibacterial activity to both Escherichia coli and Staphylococcus epidermidis. Thus, the present work has demonstrated a waste valorisation strategy that can be used to produce high-value Au nanoparticles with antimicrobial properties for use in future pharmaceuticals.